2018
DOI: 10.1111/his.13697
|View full text |Cite
|
Sign up to set email alerts
|

Lung histopathology of non‐infectious pulmonary complications after allogeneic haematopoietic stem cell transplantation

Abstract: Interstitial pathology was associated with bronchiolar lesions in 41% of the cases reviewed (n = 25). Lung airway and interstitial inflammation was still present in lung explants from patients who underwent lung transplantation for post-allogeneic HSCT end-stage respiratory insufficiency. Herein, we describe a wide spectrum of pathological lung lesions encountered in post-allogeneic HSCT NIPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 20 publications
0
30
1
Order By: Relevance
“…Initially, the main histopathological/radiological manifestation was thought to be pleuroparenchymal fibroelastosis (PPFE), defined by subpleural collagen deposition with a thickening of the alveolar septal elastic network, specifically affecting the (sub)pleural and paraseptal pulmonary compartment, especially in the upper lobes of the lung 14 . However, in a further histopathological analysis of 21 RAS cases, von der Thüsen et al found PPFE only in 10 of 21 cases, while patterns of nonspecific interstitial pneumonia, fibrinous exudates, and emphysema were also described, similar to findings post‐HSCT 33 . PPFE, however, is a terminology mostly utilized to describe a radiologic pattern, whereas the more accurate histologic description of the observed pattern of predominant subpleural and paraseptal collagenous obliteration of the alveoli with elastosis is AFE.…”
Section: Restrictive Allograft Syndromementioning
confidence: 78%
See 1 more Smart Citation
“…Initially, the main histopathological/radiological manifestation was thought to be pleuroparenchymal fibroelastosis (PPFE), defined by subpleural collagen deposition with a thickening of the alveolar septal elastic network, specifically affecting the (sub)pleural and paraseptal pulmonary compartment, especially in the upper lobes of the lung 14 . However, in a further histopathological analysis of 21 RAS cases, von der Thüsen et al found PPFE only in 10 of 21 cases, while patterns of nonspecific interstitial pneumonia, fibrinous exudates, and emphysema were also described, similar to findings post‐HSCT 33 . PPFE, however, is a terminology mostly utilized to describe a radiologic pattern, whereas the more accurate histologic description of the observed pattern of predominant subpleural and paraseptal collagenous obliteration of the alveoli with elastosis is AFE.…”
Section: Restrictive Allograft Syndromementioning
confidence: 78%
“…14 However, in a further histopathological analysis of 21 RAS cases, von der Thüsen et al found PPFE only in 10 of 21 cases, while patterns of nonspecific interstitial pneumonia, fibrinous exudates, and emphysema were also described, similar to findings post-HSCT. 33 PPFE, however, is a terminology mostly utilized to describe a radiologic pattern, whereas the more accurate histologic description of the observed pattern of predominant subpleural and paraseptal collagenous obliteration of the alveoli with elastosis is AFE. Analogous to BO, AFE could also be shown to be a general reaction to injury, which can arise due to viral or bacterial infection, but also following acute AMR, leading to a sequence of vascular and epithelial injury, intra-alveolar fibrinous exudation, aberrant macrophage accumulation and activation, failed fibrin degradation, and ultimately fully developed AFE.…”
Section: Re S Tric Tive Allog R Af T Syndromementioning
confidence: 99%
“…47 The mechanisms of drug-related pneumonitis are largely unknown but may be a result of direct cytotoxic effects, oxidative stress, or immune-mediated reactions. 48,49 Pneumonitis has also been associated with many anticancer therapies, 50 including chemotherapy (pemetrexed, 51 docetaxel, 52 bleomycin, 53 and gemcitabine 54 ), targeted therapy (epidermal growth factor receptor tyrosine kinase inhibitors 55 and anaplastic lymphoma kinase inhibitors 56 ), stem-cell transplantation, 57 and chest RT. 45 Although animal models with deregulated cytotoxic T-lymphocyteeassociated antigen 4 (CTLA-4) or PD-1 function exhibit lymphoid infiltration of the lung and other organs, 58 the mechanisms by which pneumonitis from ICB arises during or after (sometimes late after discontinuation) cancer treatment is unknown.…”
Section: Characteristics Of Pneumonitis Associated With Icb Treatmentmentioning
confidence: 99%
“…Radiographic and pathologic findings vary, depending on the underlying entity. A histopathologic study including specimens from 18 different sites showed a variety of patterns of their interstitial lesions including non-specific interstitial pneumonia (NSIP), lymphoid interstitial pneumonia (LIP), diffuse alveolar damage (DAD), and pleuroparenchymal fibroelastosis (PPFE) [ 62 ].…”
Section: Late Post-transplantation Period (>100 Days Post-transplant)mentioning
confidence: 99%